2015
DOI: 10.1093/ejcts/ezv155
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic blood transfusion in bilateral lung transplantation: impact on early function and mortality

Abstract: Unlike general cardiothoracic surgery, blood transfusion had no effect on all-cause mortality, whereas a greater administration of platelets was observed to be associated with higher adjusted 1-year mortality. Transfusion rates were not significantly influenced by pretransplant diagnoses. Interestingly, lung function at 3 and 6 months was similar for patients who received more blood product transfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 23 publications
5
28
0
Order By: Relevance
“…Platelet transfusion has been repeatedly identified as an independent risk factor for increased short-and long-term mortalities following lung transplantation (Figure 1), a signal also present in patients undergoing cardiac surgery and liver transplantation. 21,31,32 A retrospective singlecenter study by Ong et al 21 of 311 bilateral lung transplant recipients found no difference in 1-year mortality based on the amount of RBC or FFP transfused, and a HR of 2.3 for 1-year mortality in patients who had received greater than 1 unit of platelets intraoperatively. Zalunardo et al 33 also noted increased in-hospital mortality in the immediate posttransplant period in patients who had received platelets.…”
Section: Transfusion and All-cause Mortality/ Chronic Lung Rejectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Platelet transfusion has been repeatedly identified as an independent risk factor for increased short-and long-term mortalities following lung transplantation (Figure 1), a signal also present in patients undergoing cardiac surgery and liver transplantation. 21,31,32 A retrospective singlecenter study by Ong et al 21 of 311 bilateral lung transplant recipients found no difference in 1-year mortality based on the amount of RBC or FFP transfused, and a HR of 2.3 for 1-year mortality in patients who had received greater than 1 unit of platelets intraoperatively. Zalunardo et al 33 also noted increased in-hospital mortality in the immediate posttransplant period in patients who had received platelets.…”
Section: Transfusion and All-cause Mortality/ Chronic Lung Rejectionmentioning
confidence: 99%
“…The effect of RBC transfusion on long-term graft function and overall mortality, however, is less clear. One retrospective single-center study of 134 patients by Weber et al 20 found that transfusion of >4 U RBCs was associated with increased 1-year mortality, while larger studies by Ong et al 21,22 found no significant difference in 3-and Figure 1. Blood product transfusion in the peritransplant period and associations with adverse outcomes.…”
Section: Transfusion and Primary Graft Dysfunction/acute Lung Rejectionmentioning
confidence: 99%
“…The same group reported rejection episodes and 10-year mortality in another study and found no relationship to any of the blood products transfused. 53 Platelet transfusion affected early mortality but not late outcomes. Transfusions and immune modulation are known to be associated with better survival in solid organ transplantations (kidneys and heart); nevertheless, such an association was not shown in this particular study of LTX recipients.…”
Section: Blood and Blood Product Transfusionsmentioning
confidence: 99%
“…A controversial debate exists in kidney and liver transplantation regarding the significance of allosensitization from pretransplant blood transfusion . Although a recent study found that blood transfusion occurring within 24 hours of LTx had no effect on all鈥恈ause mortality or pulmonary function at 3 and 6 months, no research has investigated the influence of pretransplant transfusion of RBCs on clinical outcomes after LTx. Due to this gap in knowledge, we sought to identify differences in survival between LTx recipients who received a pretransplant transfusion on the wait list and LTx recipients who did not.…”
Section: Introductionmentioning
confidence: 99%